Biokinetics and tissue response to ultrananocrystalline diamond nanoparticles employed as coating for biomedical devices. Issue 8 (12th September 2016) - Tasat, Deborah R.; Bruno, Marcos E.; Domingo, Mariela; Gurman, Pablo; Auciello, Orlando; Paparella, María L.; Evelson, Pablo; Guglielmotti, María B.; Olmedo, Daniel G.
Abstract: Although Ultrananocrystalline diamond (UNCD) has been proposed as a coating material for titanium biomedical implants, the biological effects and toxicity of UNCD particles that could eventually detach have not been studied to date. The biokinetics and biological effects of UNCD compared to titanium dioxide (TiO2 ) nanoparticles was evaluated in vivo using Wistar rats ( n  = 30) i.p. injected with TiO2, UNCD or saline solution. After 6 months, blood, lung, liver, and kidney samples were histologically analyzed. Oxidative damage by membrane lipidperoxidation (thiobarbituric acid reactive substances‐TBARS), generation of reactive oxygen species (superoxide anion‐ O 2 − ), and antioxidant enzymes (superoxide dismutase‐SOD, catalase‐CAT) was evaluated in lung and liver. Histologic observation showed agglomerates of TiO2 or UNCD in the parenchyma of the studied organs, though there were fewer UNCD than TiO2 deposits. In addition, TiO2 caused areas compatibles with foci of necrosis in the liver and renal hyaline cylinders. Regarding UNCD, no membrane damage (TBARS) or mobilization of enzymatic antioxidants was observed either in lung or liver samples. No variations in O 2 − generation were observed in lung (Co: 35.1 ± 4.02 vs. UNCD: 48 ± 9.1, p  > 0.05). Conversely, TiO2 exposure caused production of O 2 − in alveolar macrophages and consumption of catalase ( p < 0.05). The studied parameters suggest that UNCD caused neither biochemical nor histological alterations, and therefore may prove useful as a surface coating for biomedical implants. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 105B: 2408–2415, 2017.